TEACHING HORTATORY EXPOSITION WRITING THROUGH TREE DIAGRAM TECHNIQUE - Sari, Yunita; Apriliaswati, Rahayu; Novita, Dewi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstrak: Penelitianinimenggunakanmetode quasi-experimental yang bertujuanuntukmeningkatkansiswadalammenulisteks hortatory exposition. Dalampenelitianini, teknik Tree Diagram digunakanuntukmengetahuikeberhasilanteknikinidalammenulisteksargumen. Sampelpenelitianiniadalahsiswakelas XI IPA 4 yang terdiridari 38 siswasebagaikelompokekperimendansiswakelas XI IPA 5 yang terdiridari 38 siswasebagaikelompokpengontrol di SMA Negeri 1 Sungai Raya. Hasil dari t-test adalah t-value (10,5) lebih tinggi dari t-table (2,660).Effect size dari penelitian ini adalah modest effect dimana hasil dari penghitungan adalah (0,40). Oleh karena itu, dapat di simpulkan bahwa penggunaan teknik Tree Diagramdapatmeningkatkanpenulisanteks argument siswadalammengorganisirdanmengembangkan ide-ide. Kata kunci: menulis hortatory, tree diagram, experimental Abstract: This research used a quasi-experimental to improve students hortatory exposition writing.In this research, the tree diagram technique was used to find out the effectiveness of this technique in writing hortatory exposition text.The samples were observedin this research were students of class XI IPA 4 that consisted of 38 students as the experimental group and students of class XI IPA 5 that consisted of 38 students as the control group at SMA Negeri 1 Sungai Raya.The result from t-test was that t-value (10.5) was higher than t-table (2.660). The effect size of this study was categorized as modest effect because the result of the computation was (0.40).Therefore it was concluded that the use of tree diagram technique could improve students writing hortatory exposition in developing and organizing the ideas. Keywords: writing hortatory, tree diagram,experimental